2000
DOI: 10.18800/psico.200002.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictores del desempeño en lectura y escritura de niños de primer grado

Abstract: Se evaluó el desempeño de 288 niños de primer grado en tareas de lectura y escritura de diferente grado de complejidad. Se tomaron como predictores de los desempeños en las tareas evaluadas variables asociadas con la práctica docente y con antecedentes académicos inmediatos de los niños, así como sus características físicas. Mediante la aplicación de un análisis de regresión múltiple se identificó que las variables de años de experiencia del maestro en primer grado, el juicio que emite respecto a la adquisició… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…For example, one study measured PA but also examined quality of the preschool program (Pino & Bravo, 2005 ). Another study investigated the factors that were associated with student reading ability and found that school‐level factors (e.g., teacher quality and student abilities) predicted 40% of students' academic performance, while the authors reported that home factors (e.g., poverty) account for more variance in school performance (Ramírez et al 2000 ). Refer to Table D4 in Appendix D for quality ratings for all quantitative nonintervention studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study measured PA but also examined quality of the preschool program (Pino & Bravo, 2005 ). Another study investigated the factors that were associated with student reading ability and found that school‐level factors (e.g., teacher quality and student abilities) predicted 40% of students' academic performance, while the authors reported that home factors (e.g., poverty) account for more variance in school performance (Ramírez et al 2000 ). Refer to Table D4 in Appendix D for quality ratings for all quantitative nonintervention studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the sample, 47 of the 61 studies generalized the study outcomes to the population in the study. Several studies generalized the study findings to a different grade level or age group (Ramírez, Verdugo, & Sánchez, 2000), another country (de Manrique & Signorini, 1994), or to the population in the study despite a small sample (Bandini et al, 2006). Still, others generalized to the entire population in the country (De Abreu, & Cardoso-Martins, 1998) and across countries (Abadzi, Crouch, Echegaray, Pasco, & Sampe, 2005).…”
Section: External Validitymentioning
confidence: 99%
“…Fue justamente en el ITSON en donde figuró entre el cuerpo de profesores-investigadores de tiempo completo Aldo Bazán Ramírez, quien laboró en esa institución entre 1997 y 2005; contaba con una sólida formación en la PC en su modalidad experimental y con una orientación interconductual, ya que había cursado estudios de Maestría en Metodología de la Teoría e Investigación Conductual en la FES-Iztacala, bajo el liderazgo de Emilio Ribes Iñesta. Él fue, además, en el propio IT-SON, uno de los pioneros en la publicación de trabajos de investigación con la orientación conductual (Bazán y Corral, 2001;Bazán y López, 2002;Bazán, et al, 2000), así como dos libros (Bazán, 1999;Bazán y Arce, 2002). Infortunadamente, con el retiro de Aldo Bazán Ramírez la tradición de la PC en su modalidad experimental cayó pronto en el olvido en el ITSON, a tal grado que hoy en día no hemos encontrado un solo trabajo de investigación experimental en el nivel básico, publicado por los profesores-investigadores de dicha institución.…”
Section: Introducción: Breves Antecedentes De La Psicología Conductua...unclassified